2013
DOI: 10.1634/theoncologist.2012-0455
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Carboplatin- and Cisplatin-Based Concurrent Chemoradiotherapy in Locally Advanced Cervical Cancer Patients With Morbidity Risks

Abstract: Purpose. The aim of this study was to assess the activity and toxicity of primary carboplatin-based chemoradiotherapy (CarboRT) Implications for Practice: Cisplatin-based chemoradiotherapy (CisRT) has been regarded as the standard treatment for patients with locally advanced cervical cancer. Cisplatin, however, can cause nephrotoxicity, has highly emetogenic effects, and creates the need for a large amount of hydration. Carboplatin-based chemoradiotherapy was better tolerated than CisRT without compromising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
3
12
0
1
Order By: Relevance
“…Sebastião [14] showed that single-agent cisplatin and carboplatin plus RT have similar survival benefits and toxicity. The study conducted by Nam [15] et al also supports this conclusion. For patients who cannot receive cisplatin, carboplatin may be an alternative treatment.…”
Section: Discussionsupporting
confidence: 54%
“…Sebastião [14] showed that single-agent cisplatin and carboplatin plus RT have similar survival benefits and toxicity. The study conducted by Nam [15] et al also supports this conclusion. For patients who cannot receive cisplatin, carboplatin may be an alternative treatment.…”
Section: Discussionsupporting
confidence: 54%
“…Currently, most of the data directly comparing carboplatin and CDDP as radiosensitizers are originated from small, non randomized or uncontrolled trials. Despite these limitations, one study compared both CRT regimens and demonstrated that carboplatin appears to be equally effective and less toxic than cisplatin [23]. Therefore, carboplatin may be an alternative when treating patients with multiple comorbidities or kidney dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In India, it accounts for 16% of all cancers in urban women and 37% of the cancers in rural women (3). Concurrent chemoradiation using cisplatin has shown 30-50% reduction in the risk of death, and is regarded the standard treatment for patients with cervical cancer (7,14,15). Carboplatin, an analogue of cisplatin, with a similar mechanism of action, has been used for the treatment of locally advanced cervical carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It has advantages over cisplatin in terms of decreased nephrotoxicity, neurotoxicity and emetogenesis (16). This favourable toxicity profile when compared to cisplatin may result in better patient adherence to the treatment plan (15). A phase II clinical study in patients with recurrent or metastatic squamous carcinoma of the uterine cervix revealed substantially better toxicity profile of carboplatin than cisplatin with similar efficacy (17).…”
Section: Discussionmentioning
confidence: 99%